Evaluasi Sifat Fisik Pemalsuan Dedak Padi dengan Penambahan Tongkol Jagung - Ridla Muhammad; Rima Martin; Nahrowi Nahrowi; Nahdhiyah Alhasanah; Markistiandi Fadhilah (Jurnal Ilmu Peternakan Terapan, 2022)
The objective of this study was to evaluate physical properties of rice bran forgery with corn cob addition. Corn cob mixed with rice bran by different levels 0%, 5%, 10%, 15%, and 20%. The experimental design was completely random design (CRD) with 5 treatments and 3 replications. The data were analyzed by ANOVA and followed by orthogonal contrast test if there were significant differences between the treatments. The results showed the addition of corn cob (0%, 5%, 10%, 15% and 20%) significantly (P<0.01) decreased the specific gravity (kg L-1) by 1.36, 1.32, 1.26, 1.20 and 1.16 (r = 93%), bulk density (g L-1) by 286.53, 283.02, 275.74, 268.35 and 263.86 (r = 98%), compact bulk density (g L-1) by 475.44, 463.69, 453.18, 443.14 and 433.53 (r = 99%) and angle of repose (˚) by 44.40, 43.91, 43.27, 43.15 and 42.70 (r = 93%) while the particle size (mm) increased by 1.22, 1.23, 1.23, 1.24 and 1.25 (r = 95.8%). Detection of rice bran forgery can be evaluated through physical test correlation and the highest correlation is found in the compact bulk density parameter.